VISUALISASI STUDI WIRAUSAHA WANITA MENGGUNAKAN ANALISIS BIBLIOMETRIK - Wahjoedi, Tri (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to visually investigate mapping and research trends in the field of woman entrepreneur at the international level. This study uses a bibliometric method using secondary data from Scopus. Analyze and visualize the data using the program VOS Viewer and the search results analysis feature of Scopus. This study analyzed 1392 scientific documents published between 2011 and 2021. Studies show Babson College and Kaciak, E. are the most active institutions and individual researchers in the study of woman entrepreneur. Business, management and accounting are the most managed and widely used areas of woman entrepreneurs. There are four categories of collaborative maps created by researchers around the world. Based on the identification of the knowledge accumulated over the last decade of publication, this study proposes to group the problems of woman entrepreneurs: theme of entrepreneurship & society, barrier & challenge, business performance & network, empowerment & information technology